New record and redescription of the monotypic genus Comefulvius Carvalho & Carpintero, 1985 (Hemiptera: Heteroptera: Miridae: Cylapinae) - Chérot, Frédéric; Carpintero, Diego L.; Wolski, Andrzej (Zootaxa, 2014)
Comefulvius chingonus Carvalho & Carpintero, the only representative of the genus Comefulvius, previously known only from Córdoba Province, Argentina, is recorded from Ecuador. Redescription of Comefulvius is given along with color photographs of the adult and illustrations of the male genitalia.